Dampak Intensitas Penggunaan Gadget terhadap Kemampuan Berpikir Kritis dan Literasi Peserta Didik pada Era Digital - Mellia Ristika; Yeni Sulastri (Suria Academic Press, 2026)
The rapid advancement of digital technology has significantly increased gadget use among students and transformed contemporary learning environments. While gadgets provide broad access to information and support digital learning, uncontrolled use may also create distractions and hinder the development of critical thinking and literacy skills. This article aims to conceptually examine the impact of gadget use intensity on students' critical thinking and literacy in the digital era. The study employed a conceptual review by synthesizing theories and empirical findings published in accredited national and reputable international journals between 2020 and 2025. The analysis involved literature identification, content analysis, and conceptual synthesis to explain the relationships among the main constructs. The findings indicate that the impact of gadget use intensity is not determined solely by the duration of use but is influenced by learning purposes, the quality of digital activities, self-regulation, and educational support. Gadget use for academic learning, information exploration, collaboration, and problem-solving contributes positively to the development of critical thinking and literacy. Conversely, excessive use for entertainment and non-academic activities tends to increase distraction and reduce the depth of cognitive processing. This study proposes a conceptual model integrating gadget use intensity, digital activity quality, critical thinking, and literacy to provide a theoretical foundation for developing more effective and responsible digital learning practices in the twenty-first century.